2013
DOI: 10.1038/ncomms2615
|View full text |Cite
|
Sign up to set email alerts
|

A novel metatranscriptomic approach to identify gene expression dynamics during extracellular electron transfer

Abstract: Microbial respiration via extracellular electron transfer (EET) is a ubiquitous reaction that occurs throughout anoxic environments and is a driving force behind global biogeochemical cycling of metals. Here we identify specific EET-active microbes and genes in a diverse biofilm using an innovative approach to analyse the dynamic community-wide response to changing EET rates. We find that the most significant gene expression responses to applied EET stimuli occur in only two microbial groups, Desulfobulbaceae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(144 citation statements)
references
References 46 publications
6
137
1
Order By: Relevance
“…Our previous metatranscriptomic analyses indicated that Desulfuromonadales (including genus Geobacter) and Desulfobulbus strains responded to surface potential changes by different gene expression levels of outer membrane c-type cytochromes. These significant changes in gene transcription were related to increases in EET rates when exposed to SP electropositive conditions (Ishii et al, 2013). These data suggest that different c-type cytochromes may define an affinity for microbial electron transfer to substrates with specific surface potentials.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our previous metatranscriptomic analyses indicated that Desulfuromonadales (including genus Geobacter) and Desulfobulbus strains responded to surface potential changes by different gene expression levels of outer membrane c-type cytochromes. These significant changes in gene transcription were related to increases in EET rates when exposed to SP electropositive conditions (Ishii et al, 2013). These data suggest that different c-type cytochromes may define an affinity for microbial electron transfer to substrates with specific surface potentials.…”
Section: Discussionmentioning
confidence: 65%
“…Using electrochemical approaches in MFC systems, the EET activity in a microbial community can be monitored as operational current generation, anodic limiting (maximum) current density and per-biomass electrode reducing rate throughout system operations (Ishii et al, 2008). In addition, the anode potential can be controlled by potentiostatic set-potential (SP) operation (Wagner et al, 2010), which allows acceleration or suppression of EET rates in the community as a function of applied surface redox potential (Aelterman et al, 2008;Ishii et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The KEGG orthology (KO) functional annotation has been determined for 107 marker genes that are typically found to be in single copies in more than 95% of bacterial genomes (33,34). The number of these marker genes in each Metawatt cluster was determined from the KO assignments made in the KEGG annotation of the metagenome contigs.…”
Section: Methodsmentioning
confidence: 99%
“…Several molecular studies revealed the role of pili and of multiheme outer-membrane c-type cytochromes in electron transfer (Butler et al, 2010, Lovley, 2012. A comparative metatranscriptomic analysis revealed eight genes with no annotated protein function to be related to electrochemical activity (Ishii et al, 2013). Both the fields of corrosion and microbial fuel cell research can benefit from these in-depth studies.…”
Section: Perspectivesmentioning
confidence: 99%